The effect of suturing protocols on coronally advanced flap root-coverage outcomes: A Meta-Analysis (2016)
The purpose of this systematic review and meta-analysis was to investigate whether suturing protocols (suture removal timing and/or type of suture material) influence root coverage outcomes in recession defects treated with a coronally advanced flap (CAF) procedure. Databases (MEDLINE, EMBASE) were searched for randomized clinical trials (RCTs) that assessed single-tooth, Miller Class I/II recession defects, surgically treated by CAF. Mixed-effects linear regression analysis evaluated differences on complete root coverage (CRC) between RCTs with early (<10 days postoperatively) and late (≥10 days) suture removal, as well as between RCTs using absorbable and non-absorbable sutures removed ≥10 days postoperatively. Seventeen RCTs were eligible for inclusion. Overall, data from 325 single gingival recession defects revealed a statistically significant superior proportion of sites exhibiting CRC when sutures were removed ≥10 days postoperatively compared to those in which sutures were removed <10 days (P = 0.03). Conversely, there were no significant differences in CRC outcomes between absorbable and non-absorbable sutures when they were removed ≥10 days after surgery (P = 1.00). The majority of included RCTs (59%) reported use of non-absorbable suture materials. Within the limitations of the available data, it can be concluded that early suture removal (<10 days) can negatively influence root-coverage outcomes in single-tooth defects treated by a CAF procedure. There is a strong need for studies designed specifically to investigate suturing protocols in root-coverage procedures.